Lexicography and Language Planning in 18th Century Sweden - Rogström, Lena (Lexikos, 2020)
The 18th century was important for Swedish linguistic development. Foreign lexical influence and orthographical standardization were intensely discussed, and the vocabulary was codified in several dictionaries, all bilingual. In this article, two questions of 18th century lexicography are studied in two influential dictionaries: Serenius (1741) and Sahlstedt (1773). The first question concerns the inclusion of Latin and Swedish legal lexical items in the lemma list; the second question examines the lexicographical treatment of the lexical item and the division into senses. 40 lexical items with a legal sense were extracted from the first two judicial handbooks written in Swedish (Rålamb 1674 and Kloot 1676). As a benchmark, Dalin (1850–55) was used; a monolingual dictionary representing the period when lexicography became fully developed in Sweden. Two modern dictionaries are also used as a comparison, SO (2009) and NSEOP (2018). The results indicate that both Serenius and Sahlstedt were loyal to the ideas of their time. They included only Latin lexical items that were already fully incorporated in Swedish and relevant for general dictionaries. The judicial senses are also discerned in the articles, but sense indicators are used in an inconsistent way and examples get mixed up. The lexicographers also lean heavily on Latin as meta language.